Removal of COD and ammoniacal nitrogen by banana trunk fiber with chitosan adsorbent - Suhani, Noorain; Radin Mohamed, Radin Maya Saphira; Abdul Latiff, Ab Aziz; Nasir, Nazlizan; Ahmad, Baharin; Abdulrahman Oyekanmi, Adeleke; Awang, Halizah; Daud, Zawawi (Penerbit UTM Press, 2020)
Kitchen wastewater that is discharged to the environment is one of the contributing factors to water pollution in developing countries. Adsorption is one of the emerging technology of biological treatments that is an environmentally friendly for the removal of pollutants. Banana trunk fiber with chitosan as an adsorbent was investigated for minimizing COD and ammonia from the kitchen wastewater. The raw kitchen wastewater sample used in the study was collected from the Arked food court located in Universiti Tun Hussein Onn Malaysia in Johor (Malaysia). The optimum of ratio, pH, shaking speed and contact time for COD and ammonia removal were determined. The result indicated the optimum mix ratio of fiber with chitosan, pH, shaking speed and contact time respectively was 50:50, pH 7, 125 rpm and 120 minutes based on the adsorption of COD (87%) and ammonia (90%) by banana trunk fiber with chitosan. Kinetic study of the results gave a pseudosecond order the R2 was closed to unity which was 0.998. It will significantly be considered for efficient removal of organic and nutrient pollutants present in kitchen wastewater treatment.